2006
DOI: 10.2519/jospt.2006.36.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Fibular Position in Individuals with Self-Reported Chronic Ankle Instability

Abstract: Study Design: Case control study. Objectives: The purpose of this study was to assess the position of the distal fibula in individuals with chronic ankle instability (CAI). Background: Recent literature has suggested that a positional fault of the fibula on the tibia may contribute to CAI; however, there is a lack of objective scientific evidence to support this claim. Methods and Measures: Thirty subjects with unilateral CAI (mean ± SD age, 20.3 ± 1.3 years) and 30 subjects with no previous history of ankle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 18 publications
2
50
1
Order By: Relevance
“…The present study analyzed the 3-D side-to-side difference of the position of the fibula with respect to the tibia. Although previous studies have reported fibular anteroposterior displacements in individuals with CAI, 2,15,29,30,50,54 the current study did not. Because anteroposterior displacement of the fibula may be related to the severity of lateral ankle ligament injury, further study that distinguishes the severity of lateral ankle sprain or the presence of mechanical instability is required.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The present study analyzed the 3-D side-to-side difference of the position of the fibula with respect to the tibia. Although previous studies have reported fibular anteroposterior displacements in individuals with CAI, 2,15,29,30,50,54 the current study did not. Because anteroposterior displacement of the fibula may be related to the severity of lateral ankle ligament injury, further study that distinguishes the severity of lateral ankle sprain or the presence of mechanical instability is required.…”
Section: Discussioncontrasting
confidence: 77%
“…2,15,50 In contrast, other studies using radiography have noted the presence of fibular anterior translation in the ankles with CAI. 29,30,54 Thus, there is no consistent reported pattern of fibular malalignment in the anteroposterior direction and, to our knowledge, no previous study has considered mediolateral malalignment. Most lateral ankle sprains involve injury to the lateral ankle ligaments (eg, the anterior talofibular or calcaneofibular ligament).…”
Section: T T Conclusionmentioning
confidence: 75%
See 1 more Smart Citation
“…These findings suggest that targeting potential arthrokinematic restrictions of posterior talar glide results in comparatively greater improvement in range of motion initially and supports the hypothesis that ankle sprains may cause positional faults of the talus and fibula. (20, 41) As well, based on the changes reported, the joint mobilization group had a two-fold increase in dorsiflexion improvement at 2 weeks, but the variability of this improvement also increased. This suggests that 2 weeks of either STARS may be effective in enhancing dorsiflexion.…”
Section: Discussionmentioning
confidence: 91%
“…Restrictions in talocrural joint and distal tibiofibular joint mobility have been shown to occur in individuals with a history of lateral ankle sprain (Denegar et al, 2002;Whitman et al, 2009) and may be due to the slight anterior displacement of the fibula relative to the tibia (Hubbard and Hertel, 2008;Hubbard et al, 2006). This displacement is thought to occur due to lengthening or disruption of the anterior talofibular ligament (Denegar et al, 2002).…”
Section: Introductionmentioning
confidence: 96%